أثر أبعاد تجربة العلامة التجارية على الولاء الموقفي والولاء السلوكي -دراسة تجريبية على سيارات هيونداي -: The impact of brand experience dimensions on attitudinal and behavioral loyalty - An empirical study on Hyundai cars - - شريفي جل ول; إدريسي مختار (Journal of North African Economies, 2025)
This current study’s primary purpose was to empirical research on the impact of brand experience dimensions (i.e., sensory, affective, behavioral, and intellectual) on attitudinal loyalty and behavioral loyalty of Hyundai cars brand. We analyzed data from 200 customers who had purchased Hyundai cars. The data was tested through partial least squares structural equation modeling SmartPLS3 program. The findings of study revealed that brand experience dimensions had substantial positive impact on both attitudinal loyalty and behavioral loyalty.